Effect of Amla (Phyllanthus emblica) Extract on Fresh and Cryopreserved Seminal Attributes of Jamnapari Buck - Kumar, Vikas; Srivastava, Sushant; Alam, Kabir; Kumar, Rabindra; Kumar, Rajesh; Kumar, Pramod (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
The aim of the present study was to determine the effect of an ethanolic extract of Phyllanthus emblica (Amla) fruit on the quality of goat semen after the freezing-thawing process. Twelve ejaculates collected from two Jamnapari bucks were evaluated. Semen samples were split-diluted with a Tris-based extender containing the additive ethanolic extract of Phyllanthus emblica fruit (0.6 and 0.9%) and an extender containing no additive (control); were filled in 0.25 mL French straws, and equilibrated for 4 h at 4o C and frozen in liquid nitrogen vapour. Frozen straws were thawed individually at 37o C for 30 s in a water bath. The samples were evaluated for sperm quality parameters at pre-freeze (on dilution) and post-thaw stages. The freezing extender supplemented with 0.6 and 0.9% ethanolic extract of Phyllanthus emblica fruit led to significantly higher percentages of post-thawed sperm motility, livability, and plasma membrane integrity with reduced percentage of sperm abnormalities and seminal plasma enzyme activities in comparison to the controls (p < 0.001). The study showed that adding 0.6% and 0.9% ethanolic extract of Phyllanthus emblica fruit to the extender (Tris-citric-acid-fructose-egg yolk-glycerol) improved the quality of post-thawed Jamnapari buck semen. The highest preservation efficiency was observed in 0.6% ethanolic extract compared to other treatments.